2020
DOI: 10.1093/cid/ciaa882
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Nasopharyngeal and Midturbinate Nasal Swab Testing for the Identification of Severe Acute Respiratory Syndrome Coronavirus 2

Abstract: Testing of paired mid-turbinate (MT) nasal and nasopharyngeal (NP) swabs, collected by trained personnel from 40 patients with COVID-19 showed more NP (76/95, 80%) than MT swabs tested positive (61/95, 64%; p=0.02). Among samples collected a week after study enrollment, fewer MT than NP samples were positive (45% vs 76%; p=0.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 11 publications
5
59
1
Order By: Relevance
“…We are aware of two studies comparing sensitivity of MT and NP swabs for SARS-CoV-2 detection. 2,3 Pinninti et al, in inpatients similar to ours, reported NP swabs as more sensitive than MT swabs (80% vs. 64% overall), with difference in sensitivity increasing with time from illness onset. 3 However, our difference in sensitivity between NP and MT swabs was statistically significant even in the first week of illness, while that of Pinninti et al was not.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We are aware of two studies comparing sensitivity of MT and NP swabs for SARS-CoV-2 detection. 2,3 Pinninti et al, in inpatients similar to ours, reported NP swabs as more sensitive than MT swabs (80% vs. 64% overall), with difference in sensitivity increasing with time from illness onset. 3 However, our difference in sensitivity between NP and MT swabs was statistically significant even in the first week of illness, while that of Pinninti et al was not.…”
Section: Discussionsupporting
confidence: 73%
“…2,3 Pinninti et al, in inpatients similar to ours, reported NP swabs as more sensitive than MT swabs (80% vs. 64% overall), with difference in sensitivity increasing with time from illness onset. 3 However, our difference in sensitivity between NP and MT swabs was statistically significant even in the first week of illness, while that of Pinninti et al was not. In an outpatient setting, Tu et al found that NP swabs detected all 52 patients with either swab positive, while MT swabs detected 50.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…2,11,15 One of the major studies to discredit the performance of the ID NOW compared dry nasal swabs (tested on the ID NOW) to nasopharyngeal swabs (tested on Cepheid Xpert Xpress), which is an inappropriate comparison given the superiority of positivity rate among nasopharyngeal specimens to nasal specimens. 19,21 Furthermore, Basu et al tested patients with symptom onset up to 1 month from time of sample collection, and it is unclear how many patients with confirmed COVID-19 had symptoms ≤ 7 days. 3 Among the studies that adhered to current ID NOW manufacturer recommendations for testing, ID NOW PPA was 66.7% and 94.1%.…”
Section: Resultsmentioning
confidence: 99%
“…(4) Identifying acute infection with SARS-CoV-2 virus is carried out via nucleic acid ampli cation testing (such as real-time reverse transcriptase polymerase-chain reaction) and specimens are most often obtained from the respiratory tract. (5,6) Several studies have compared the effectiveness of nasopharyngeal swabs to oropharyngeal (7)(8)(9), nasal (7,10,11), and mid-turbinate (11,12) specimens, with nasopharyngeal swabs being most sensitive. As such, the nasopharyngeal swab is currently considered the gold standard for screening specimen collection of SARS-CoV-2 (5-7, 10, 12, 13) and remains the recommended site of collection by the Canadian Public Health Laboratory Network Best Practices for COVID -19.…”
Section: Introductionmentioning
confidence: 99%